Divergent Learning In The Management Of Economic Or Social Projects For Young Students - Marleny, Sernaqué Barrantes; Angélica, Atoche Silva Luz; Graciela, Talledo Mendoza Gulissa; Julia, Morocho Ricalde Carmen; Tomasita, Herrera Mogollón Rosa (Migration Letters, 2024)
The objective of this research is to determine the effect of the divergent learning program on the management of economic or social projects in students of an Educational Institution in Piura, 2023. Research with a quantitative approach, experimental type and pre-experimental design. We worked with a population of 102 students and a single sample of 34 students, to whom the survey technique was applied and as an instrument the 28-item questionnaire to measure the dependent variable, which has a reliability of Cronbach’s Alpha with 0.821 and a validity with Aiken’s V of 0.92. The results in the pretest indicated that there is poor project management in the students because 100% of them were located at the beginning level, unlike the post test, where 62% of students were located at the achieved level. Likewise, the application of the divergent learning program optimized the management of economic and social projects due to the significant differences found (73.59) between the pre and post test (T student = 33.194, p value = 0.000). It is concluded that the program emerged significant effects in the management of economic and social projects in the students.